Change of command - Moon, Elizabeth (Riverdale, NY : Baen Books ; New York, NY : Distributed by Simon & Schuster, 2000)
The continuing saga of a dictatorial family in space. They are the Familias Regnant and they must handle a riot on a prison planet, a controversy over rejuvenating drugs with nasty side effects, and the murder of one of their members.
"A Baen Books original"--T.p. verso.
Keywords: Space warfare -- Fiction; Science fiction